Public sector investment in the direct development of urban housing in Sri-Lanka (Ceylon) - Joachim, Michael E. (The University of Edinburgh, 1973)
1. The purpose of this study is to analyse the role of public sector investment in housing in Ceylon, with the objective of achieving a solution to the housing problem.

Since there exists a distinct difference between the urban and rural areas, the study was narrowed down to the urban sector. Housing in its entirety covers the residential environment, and hence the field of analysis was narrowed down to the net residential area, hereafter called the direct development of housing.

Thus the title of this thesis 'Public sector investment in the direct, development of urban housing in Ceylon,

2. This study sets out to answer three basic questions. They are - (1) should the public sector invest in the direct development of urban housing in Ceylon? (2) If the public sector is to invest in the direct development of urban housing in Ceylon, what should be its objectives ? And (3) how can these objectives be achieved?

3. In order to answer the three questions posed the study was divided into four main parts

Part I is divided into two chapters. Chapter 1 defines terminology a3 will be understood in this study. This ohapter is of importance in understanding the subsequent chapters, and in clearing the ambiguity that may exist between the terms used in this study and in the field of pure economics. Chapter 2 is of vital importance, since it is on this chapter that the rest of the study is based.

In a mixed economy like Ceylon one is faced with the basic question - can the private sector achieve the level of Investment both in monetary and physical terms to provide adequate housing for the population, or is it necessary for the public sector to step in. The answer follows logically that if the private sector cannot do it, then the public sector must step in. Hence the need to develop a method of analysis, which is referred to in Part II, Chapter 3.

The second part of Chapter 2 deals with the objectives of public sector investment. Three basic objectives were set out. They were - (1) to solve the housing problem: (2) to do so at minimum physical costs, and (3) to maximise economic growth via the investment.

The analysis in this chapter leads to the conclusions that the housing problem is one of two parts, a physical problem defined by a set of standards, and a social problem that arises due to the unsuitability of this particular set of stan ards. Hence solving the housing problem meant defining standards which were related to the social, economic and cultural values of the population. The second objective was thus achieved since the standards defined were the minimum required. However, the costs involved had to be reduced within the limits of technology. An analysis of the third objective showed that the maximisation of economic growth in Ceylon via investment in housing could be achieved by maximising the marginal rate of employment generation, and minimising the rate of foreign exchange consumption.

Using this detailed analysis it was thus possible to approach Parts II, III and IV of the study.

4. Part n is divided into two chapters. In Chapter 3 a method of analysis was developed, which explained variation in invootmont patterns by the public and private sectors, both in the urban and rural areas, with reference to national policy from the year 1967 onwards. Using these trends it was possible to predict future investment patterns, and thus conclude that public sector investment was absolutely necessary. The method of analysis developed should be of immense use for other developing countries, since it is com¬ prehensive and inoludoa the contribution of oolf help housing in achieving tho national targets set out.

Chapter 4 uses the conclusions drawn in Chapter 3 as a basis on which a model for financing the direct development of housing both urban and rural is developed. The conclusion reached showed that by diverting private sector resources in the form of savings such as compulsory savings, and provident funds, the level of investment could be achieved, and even the backlog cleared.

5. Part III of the study is divided into two chapters. Chapter 5 deals with achieving the objective of maximising economic "growth by maximising marginal employment generation, and minimising the marginal rate of foreign exchange consumption. The whole problem is analysed via a theoretical model, and is then applied to Ceylon.

The main conclusion showed that though aided self help housing may help in solving the housing problem, it can have detrimental effects on employ¬ ment generation. In Ceylon this can be disastrous where unemployment is about 15% of the labour force. Hence self help housing should bo used with great care and is most suitable for areas of high employment, and where the ratio of housing to income is high.

In Chapter 6 the analysis sets out to define a concept for solving the housing problem at minimum physical costs. A theoretical analysis baaed on the principles of costs and benefits showed that if a housing programme is based on social, economic and cultural oharacteristics of a population, this objective could be achieved.

The main conclusion was that the concept of "housing need " did not achieve a solution at minimum physical costs, and thus the concept of "housing demand" was proposed which formed the basis on which public sector invest¬ ment should view the problem at the urban scale.

6, Part IV uses the concept of demand to achieve the objectives at the urban scale. In Chapter 7, which is theoretical in its approach, a detailed model for guiding public sector investment at the urban scale is developed. This model is applicable to all developing countries, with slight modifications, and describes for the first time a mathematically integrated approach of viewing the costs and benefits of housing to the consumer.

This model was calibrated using original data obtained by surveying approximately 1200 households in the city of Colombo, and collecting hitherto unpublished data regarding the housing construction industry in Ceylon. Chapter 8 is devoted to developing standards. This is the first time any reasonable set of standards has been developed exclusively for Ceylon.

Chapter 8 is devoted to an analysis of the costs of housing and uses data obtained in Ceylon for developing models that can be used for evaluating the different types of housing, at different locations. A most startling revelation was that it is cheaper to house larger households than smaller ones, and that flats are absolutely out of the question for urban Ceylon, cost wise.

Chapter 10 analyses the ability of a household to pay for housing, and is used in conjunction with the conclusions of Chapter 9 to define residential belts, which become basic information for the preparation of an urban plan.

Deviations from the theoretical predictions explained therein are quite revealing.

Overall the purpose of Chapters 8, 9 and 10, are to test the validity of the theoretical model, and set the base for future research. Chapter 11 describes briefly how this model can be of practical use in guiding public sector investment.

7. In conclusion the simple thesis that evolves quite conclusively from this study is that 'The public sector must play a major role in the direct development of uxban housing in Ceylon, and to achieve its objective it must define the parameters of a programme on the social, economic and cultural characteristics of its population, i. e. ruse the concept of housing demand.

There are numerous sub theses that come out of this study, which it is hoped will be of use to the developing countries in general.